Postprandial lipemia induces endothelial dysfunction and higher insulin resistance in healthy subjects (2011)
Objective: To assess the effect of postprandial lipemia on endothelial function, insulin resistance, and lipid profile in healthy subjects. Patients and methods: A prospective', interventional study in 14 healthy young men aged 18-25 years who were given a high-fat meal. Endothelial function was measured using flow-mediated dilation (FMD) in the brachial artery, flow velocity, mean arterial pressure and serum nitrite/nitrate levels (NO 2/NO 3). Glucose, insulin, total cholesterol, and triglyceride levels were also tested.